A paradigm for understanding trust and mistrust in medical research: The Community VOICES study. Issue 1 (2nd January 2018) - Smirnoff, M.; Wilets, I.; Ragin, D. F.; Adams, R.; Holohan, J.; Rhodes, R.; Winkel, G.; Ricci, E. M.; Clesca, C.; Richardson, L. D.
ABSTRACT: Background : To promote justice in research practice and rectify health disparities, greater diversity in research participation is needed. Lack of trust in medical research is one of the most significant obstacles to research participation. Multiple variables have been identified as factors associated with research participant trust/mistrust. A conceptual model that provides meaningful insight into the interplay of factors impacting trust may promote more ethical research practice and provide an enhanced, actionable understanding of participant mistrust.Methods : A structured survey was developed to capture attitudes toward research conducted in emergency situations; this article focuses on items designed to assess respondents' level of trust or mistrust in medical research in general. Community-based interviews were conducted in English or Spanish with 355 New York City residents (white 42%, African American 29%, Latino 22%).Results : Generally favorable attitudes toward research were expressed by a majority (85.3%), but many respondents expressed mistrust. Factor analysis yielded four specific domains of trust/mistrust, each of which was associated with different demographic variables: general trustworthiness (older age, not disabled); perceptions of discrimination (African American, Latino, Spanish language preference); perceptions of deception (prior research experience, African American); and perceptions of exploitation (less education).Conclusions : The four domains identified in the analysis provide a framework for understanding specific areas of research trust/mistrust among disparate study populations. This model offers a conceptual basis for the design of tailored interventions that target specific groups to promote trust of individual researchers and research institutions as well as to facilitate broader research participation.